2022
DOI: 10.1002/eom2.12180
|View full text |Cite
|
Sign up to set email alerts
|

A multicell structural battery composite laminate

Abstract: Multifunctional materials facilitate lightweight and slender structural solutions for numerous applications. In transportation, construction materials that can act as a battery, and store electrical energy, will contribute to realization of highly energy efficient vehicles and aircraft. Herein, a multicell structural battery composite laminate, with three state-of-the-art structural battery composite cells connected in series is demonstrated. The experimental results show that the capacity of the structural ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…[220][221][222] It is conceivable that the fibre-shaped LIBs can form fabric LIBs and be further woven into cloths and other textiles. 223,224 However, the fibre/textile LIBs should be further optimized in the energy density and the electroconnection when integrating with the other textile devices.…”
Section: Cell-level Designmentioning
confidence: 99%
“…[220][221][222] It is conceivable that the fibre-shaped LIBs can form fabric LIBs and be further woven into cloths and other textiles. 223,224 However, the fibre/textile LIBs should be further optimized in the energy density and the electroconnection when integrating with the other textile devices.…”
Section: Cell-level Designmentioning
confidence: 99%
“…Multicell SSC demonstrators have been manufactured, including an automotive boot lid 7 (Figure 2(b)) and a fuselage rib that powers a desktop-scale aircraft door to open and close 16 (Figure 2(c)). Hence, SSCs are at technology readiness level (TRL) four, i.e., “component validation in a laboratory environment.”
Figure 2.Previous structural power demonstrators (a) panel with integrated SBCs 15 ; (b) Volvo boot lid with integrated SSCs 7 ; (c) fuselage rib with integrated SSCs. 16
…”
Section: Introductionmentioning
confidence: 99%
“…The device chemistry has often used thermoset polymers, so methods such as prepregging, liquid resin or film infusion have been used for SSCs, whilst SBCs have been manufactured by hand lay-up inside a glovebox or with liquid resin infusion. 8,9 A multicell laminate consisting of three SBC cells in series integrated into a CFRP laminate has been demonstrated (Figure 2(a)) 15 with the following multifunctional properties: elastic modulus E = 25 GPa, strength σ = 312 MPa, Γ * = 24 Wh/kg and P * = 9.6 W/kg. 9 In parallel, an electrochemical actuator laminate, akin to an SBC, with E = 100 GPa has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a), which can achieve the multifunctional performance of electrochemical energy storage and withstand mechanical loading, attracting more and more attention. [2][3][4][5] Although several research groups have carried out many inventive studies on structural batteries, 6,7 previously reported studies are typically focused on unsafe structural lithium-ion batteries [8][9][10][11] with a composite electrode, fabricated by the following process: the slurry of the active material is coated on carbon ber fabric and dried. Although residual stress will not exist, due to the poor binding force originating from the polymer binder, such as poly(vinylidene uoride), between the solid-solid interface of active materials and the current collector, the powder active materials cannot maintain their integrity and usually fall off from the carbon ber under external load, 12,13 vividly depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%